Brain training with non-action video games enhances aspects of cognition in older adults: a randomized controlled trial - Ballesteros, Soledad; Prieto, Antonio; Mayas, Julia; Toril, Pilar; Pita, Carmen; Ponce de León, Laura; Reales, José M.; Waterworth, John (Frontiers in Aging Neuroscience, 2014)
Age-related cognitive and brain declines can result in functional deterioration in many cognitive domains, dependency, and dementia. A major goal of aging research is to investigate methods that help to maintain brain health, cognition, independent living and wellbeing in older adults. This randomized controlled study investigated the effects of 20 1-hr non-action video game training sessions with games selected from a commercially available package (Lumosity) on a series of age-declined cognitive functions and subjective wellbeing. Two groups of healthy older adults participated in the study, the experimental group who received the training and the control group who attended three meetings with the research team along the study. Groups were similar at baseline on demographics, vocabulary, global cognition, and depression status. All participants were assessed individually before and after the intervention, or a similar period of time, using neuropsychological tests and laboratory tasks to investigate possible transfer effects. The results showed significant improvements in the trained group, and no variation in the control group, in processing speed (choice reaction time), attention (reduction of distraction and increase of alertness), immediate and delayed visual recognition memory, as well as a trend to improve in Affection and Assertivity, two dimensions of the Wellbeing Scale. Visuospatial working memory (WM) and executive control (shifting strategy) did not improve. Overall, the current results support the idea that training healthy older adults with non-action video games will enhance some cognitive abilities but not others. Trial Registration: ClinicalTrials.gov identifier NCT02007616 http://clinicaltrials.gov/show/NCT02007616